When I say psychological debriefing. Issue 11 (23rd June 2021) - Teodorczuk, Andrew; Kelly, Brian; Carney, Stuart
Abstract : Critically analyzing the term 'psychological debriefing' and its evidence base yields caution against widespread adoption in medical education practice